Smart LeoBOT - Shaiful Azrul, Raysha Irdina; Shaiful Azrul, Rayyan Rantissi (Universiti Teknologi MARA, Kedah, 2022)
Artificially intelligent humanoid robots have permeated practically every part of life, including libraries, and can carry out tasks at the library that people are unable to carry out more effectively. This project design has investigated artificial intelligence (AI) humanoid robots for library book searching services in school libraries. This project design aims to discuss AI and show how it relates to robotics in libraries.